Pengaruh Struktur Modal Dan Profitabilitas Terhadap Kualitas Laba (Sub Sektor Makanan Dan Minuman Di Bei 2019-2023) - Ahmad, Hardianti; Sundarta, H. M. Imam; Abdul Syukur, R. Dudung (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of capital structure and profitability on earnings quality in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The population in this study consists of 20 food and beverage companies listed on the IDX. Using a purposive sampling technique, a total of 100 observational samples were obtained over five years of observation. This research employs a quantitative approach with secondary data obtained from the companies’ annual financial statements. Data analysis was conducted using multiple linear regression, with t-tests to examine partial effects and an F-test to examine simultaneous effects. The results show that capital structure has a positive and significant effect on earnings quality, with a significance value of 0.001 < 0.05 and a t-value of 3.5 > t-table 1.99. Profitability also has a positive and significant effect on earnings quality, with a significance value of 0.003 < 0.05 and a t-value of 3.0 > t-table 1.99. Simultaneously, capital structure and profitability significantly affect earnings quality, with an F-test significance value of 0.000 < 0.05. The study concludes that optimal management of capital structure and profitability can enhance the earnings quality of food and beverage companies